2016
DOI: 10.2119/molmed.2016.00211
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Paradox, Obesity Orthodox, and the Metabolic Syndrome: An Approach to Unity

Abstract: 1Obesity paradox, obesity orthodox, and the metabolic syndrome: An approach to unity 1 Obesity paradox and the metabolic syndrome. Abstract: 26Obesity and the accompanying metabolic syndrome are strongly associated with heightened morbidity 27 and mortality in older adults. In our review of more than 20 epidemiologic studies of major infectious 28 diseases, including leaders such as tuberculosis, community-acquired pneumonia, and sepsis, obesity was 29 associated with better outcomes. A cause-and-effect rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…These disorders are considered to be consequences of the metabolic syndrome. While the late Gerald Reaven, a leader and pioneer in the field, focused on insulin resistance as a key element strongly related to obesity, later investigators emphasized elements of inflammation, eg, pro‐inflammatory cells and cytokines—in the etiology of the metabolic syndrome . Obesity, insulin resistance, and inflammation inter‐relate and interact on the path to the late chronic disorders …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These disorders are considered to be consequences of the metabolic syndrome. While the late Gerald Reaven, a leader and pioneer in the field, focused on insulin resistance as a key element strongly related to obesity, later investigators emphasized elements of inflammation, eg, pro‐inflammatory cells and cytokines—in the etiology of the metabolic syndrome . Obesity, insulin resistance, and inflammation inter‐relate and interact on the path to the late chronic disorders …”
Section: Introductionmentioning
confidence: 99%
“…The negative effects of obesity are linked to the metabolic syndrome . The health benefits associated with obesity are often treated with suspicion and gathered under the rubric of the “obesity paradox.” The word “paradox” in the Oxford English Dictionary is “a statement or tenet contrary to received opinion or belief, especially one that is incredible, absurd, or fantastic.” Thus, the name “obesity paradox” given to the health benefits of obesity can be misleading. Benefits are not really paradoxical to the detrimental health effects of overweight.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Roth et al., in their review of over 20 epidemiological studies, found that obesity was associated with better outcomes from infections such as tuberculosis, community-acquired pneumonia and sepsis [39]. They argue that aspects of the metabolic syndrome often found in obesity provide an advantageous niche for immune cells to fight off infection.…”
Section: Introductionmentioning
confidence: 99%